The Era of COVID-19: Restrictive Measures of States and the Claims of Foreign Investors - I. M. Lifshits; A. V. Shatalova (Московский журнал международного права, 2022)
INTRODUCTION: In December 2019, an outbreak of coronavirus infection (SARS-CoV-2) was registered in Wuhan (China). Within a few months, the virus spread across Europe and Asia, and later around the world. Due to the emergency situation, the States were forced to implement various restrictive measures, including the closure of borders and public places to visit. Tese measures may lead to claims to investment tribunals from foreign investors for the protection of their rights.MATERIALS AND METHODS: Te authors researched the provisions of bilateral investment treaties, case law of international courts and tribunals in connection with national measures to protect health and the environment, as well as the manuscripts of Russian and foreign scholars. Te methodological basis of the research contains general scientifc and special methods.RESEARCH RESULTS: Te authors analyze the possibility of treatment of restrictive measures taken by States as self-judging clauses, as well as the possibility of applying Article 25 (necessity) of the Articles on Responsibility of States for Internationally Wrongful Acts as the circumstances precluding the wrongfulness. It is stated that it is undesirable to treat states’ measures as self-judging clauses, since such a treatment will provide States with too wide opportunities for exemptions from the international investment protection regime. At the same time the treatment of public health protection and prevention of economic (fnancial) crisis as an essential interest that the state safeguards against a grave and imminent peril is controversial for the purposes of applying art. 25 of the Articles on Responsibility.DISCUSSION AND CONCLUSIONS: Te authors propose to establish certain standards or principles that may be used by investment tribunals in the course of proceedings in order to assess measures taken by States. Tese principles are legality and proportionality, consistensy with the purpose and non-discrimination. Te principles can be interpreted with respect to the case law of investment tribunals for disputes on the limitation of fundamental human rights and freedoms (the right to health protection and the right to a favorable environment). Te principles can be consolidated in the model protocol to investment treaties (Memorandum of Understanding), developed under the auspices of UNCITRAL.